2008
DOI: 10.1016/j.jpcs.2008.06.096
|View full text |Cite
|
Sign up to set email alerts
|

Spin Hall effect in Sr2RuO4 and transition metals (Nb,Ta)

Abstract: We study the intrinsic spin Hall conductivity (SHC) and the d-orbital Hall conductivity (OHC) in metallic d-electron systems based on the multiorbital tight-binding model. The obtained Hall conductivities are much larger than that in p-type semiconductors. The origin of these huge Hall effects is the "effective Aharonov-Bohm phase" induced by the signs of inter-orbital hopping integrals as well as atomic spin-orbit interaction. Huge SHC and OHC due to this mecahnism is ubiquitous in multiorbital transition met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Recently, we proposed a new mechanism for the giant SHE originating from the d-orbital degrees of freedom, which is absent in semiconductors [288,289,291]. In a multiorbital system, a conduction electron acquires the 'effective Aharonov-Bohm phase factor' due to d-atomic angular momentum, as explained in figure 40.…”
Section: Unconventional Transport Phenomena In Multiorbital Systems: ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we proposed a new mechanism for the giant SHE originating from the d-orbital degrees of freedom, which is absent in semiconductors [288,289,291]. In a multiorbital system, a conduction electron acquires the 'effective Aharonov-Bohm phase factor' due to d-atomic angular momentum, as explained in figure 40.…”
Section: Unconventional Transport Phenomena In Multiorbital Systems: ...mentioning
confidence: 99%
“…In a multiorbital system, a conduction electron acquires the 'effective Aharonov-Bohm phase factor' due to d-atomic angular momentum, as explained in figure 40. We studied the SHEs in Sr 2 RuO 4 [288], which is the first theoretical study of the SHE in d-electron systems, in Pt [289] and in various 4d and 5d transition metals [291]. It is found that the explanation in figure 40 seems to capture the characteristics of SHE in d-electron systems.…”
Section: Unconventional Transport Phenomena In Multiorbital Systems: ...mentioning
confidence: 99%
“…The Fermi energy of the layered perovskite oxide Sr 2 RuO 4 contains two the Ruthenium one-dimensional orbitals d xz and d yz and one two-dimensional orbital d xy [25][26][27][28]. The four-fold rotational crystal symmetry of this material causes that the d xz and d yz orbitals behave as a doublet whereas the d xy orbital to be a independent one.…”
Section: Methodsmentioning
confidence: 99%